Implementasi Permainan Outbound Dalam Meningkatkan Kecerdasan Kinestetik Anak Usia Dini di TK Al-Hikmah Aer Bale (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The aim of this research is to find out: (1) the implementation of outbound games in improving the kinesthetic intelligence of early childhood at Al-Hikmah Aer Bale Kindergarten. The type of research used is Classroom Action Research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. This research was carried out at Al-Hikmah Aer Bale Kindergarten. The data sources in this research were divided into two, namely (1) primary data, namely Al-Hikmah Aer Bale Kindergarten children, (2) secondary data, namely Al-Hikmah Aer Bale Kindergarten teachers. Data collection techniques in this research were obtained through observation, written tests and documentation. The data analysis technique in this research is a qualitative data analysis technique. Based on the results of classroom action research that has been carried out by researchers, it can be concluded that children's kinesthetic intelligence through the outbound jump rope game overall increases with each cycle. From the pre-cycle data Not Yet Developing (BB) there were 8 children or 42.11%, while the kinesthetic intelligence of children Starting to Develop (MB) was 8 children or 42.11%, the kinesthetic intelligence of children was Developing According to Expectations (BSH) 2 children or 10.53 %, while the child's kinesthetic intelligence is Very Well Developed (BSB) 1 child or 5.26%, whereas in the first cycle there were no children who obtained Not Yet Developed (BB) kinesthetic intelligence, while the child's kinesthetic intelligence Starting to Develop (MB) was 1 child or 5, 26%, children's kinesthetic intelligence developed according to expectations (BSH) 14 children or 73.68%, while children's kinesthetic intelligence developed very well (BSB) 4 children or 21.25%, and in cycle II kinesthetic intelligence had not yet developed (BB) not there are children, while the children's kinesthetic intelligence is starting to develop (MB there are no children, the children's kinesthetic intelligence is developing according to expectations (BSH) 2 children or 10.53%, while the children's kinesthetic intelligence is developing very well (BSB) 17 children or 89.47%.